Synthesis and antitubercular activity of 4-oxo-thiazolidine derivatives of 2-amino-5-nitrothiazole - R. Sharma; P. Samadhiya; S.K. Srivastava (Bulletin of the Chemical Society of Ethiopia, 2013)
New series of N-[3-(2-amino-5-nitrothiazolyl)-propyl]-2-(substituted phenyl)-4-oxo-5-(substituted benzylidene)-1,3-thiazolidine-carboxamide, 5(a-j) have been synthesized from 2-amino-5-nitrothiazole as a starting material. The structure of all the synthesized compounds were confirmed by chemical and spectral analyses such as IR, 1H NMR, 13C NMR and FAB-Mass. All the final synthesized compounds 5(a-j) were screened for their antibacterial and antifungal activities against some selected bacteria and fungi with their MIC values and antitubercular activity screened against M. tuberculosis.